POTENSI DAN KEBUTUHAN AIRTANAH BAGI PENDUDUKDI DAERAH PENAMBANGAN GALIAN C KECAMATAN BALEENDAHKABUPATEN BANDUNG - Kiki Rejeki, - (2009)
This research is caused by the role of water is essential for the life of living creatures, especially humans. Water is a fundamental need for people. Water is not only needed by the people but also by other living creatures. Population growth is very rapid automatically will influence on the increasing demand for water. While water distribution is often uneven in many areas. When the lack of water, would be the emergence of social problems. The formulation of the problem in this research are: (1) How can potential ground water in the C extractive mining and surrounding areas?, 2) What is the water needs for communities in the C extractive mining and surrounding areas can be covered? , (3) What are the efforts made to meet water needs in the C extractive mining and surrounding areas? The Method used in this research is explorative method. The needs ground water and potential for population in the c extractive mining of Baleendah requires data such as the well depth (m), Altitude wells (m dpl), water table depth (m), the type of rock and soil material, the level of population growth and the average of ground water needs in the district Baleendah using the standard water needs according to Directorate General Cipta Karya (1982), is 60 liters / year. Furthermore, the result of the interview about the social and ground water quality are necessary. The results of research by taking samples in the three villages namely Wargamekar, Manggahang, and Andir indicate potential ground water in the mining area is still adequate. The number of residents in three villages in which 70,815 people. By taking the average needs of the population using the standard water needs according to Directorate General Cipta Karya (1982), is 60 liters / day / person, so the needs Ground water per year surplus of 1,550,848,000 liters of 1,729,220 liters of year. When population growth naturally ignore the existence of other factors such as industry and the migration of population from outside, then the potential is sufficient ground water for around 20 years. The amount of potential ground water in these villages could be reduced. Therefore, the population must take the advantages of water wisely. In addition, it is necessary for conservation efforts so can the water potential can be awaken and maintained. While the results of laboratory tests showed water quality in the area is less feasible to use for daily needs such as cooking and drinking.